Global control of hepatitis B virus: does treatment-induced antigenic change affect immunization? - C John Clements; Ben Coghlan; Mick Creati; Stephen Locarnini; Richard S Tedder; Joseph Torresi
Since its widespread introduction, the hepatitis B vaccine has become an essential part of infant immunization programmes globally. The vaccine has been particularly important for countries where the incidence of hepatitis B virus-related hepatocellular carcinoma is high. Effective treatment options for individuals with chronic hepatitis B infection were limited until 1998 when lamivudine, the first nucleoside analogue drug, was introduced. As a single treatment agent, however, lamivudine has a significant drawback: it induces lamivudine-resistant hepatitis B virus strains that may pose a risk to the global hepatitis B immunization programme. Mutations associated with drug treatment can cause changes to the surface antigen protein, the precise part of the virus that the hepatitis B vaccine mimics. However, the emergence of antiviral drug-associated potential vaccine escape mutants (ADAP-VEMs) in treated patients does not necessarily pose a significant, imminent threat to the global hepatitis B immunization programme. Nonetheless, there is already evidence that current treatment regimens have resulted in the selection of stable ADAP-VEMs. Treatment is currently intended to prevent the long-term complications of hepatitis B virus infection, with little consideration given to potential adverse public health impacts. To address individual and public health concerns, trials are urgently needed to find the optimal combination of existing drugs that are effective but do not induce the emergence of ADAP-VEMs. This paper examines the mechanism of antiviral drug-selected changes in the portion of the viral genome that also affects the surface antigen, and explores their potential impact on current hepatitis B immunization programmes.